Devil's battle - Anderson, Taylor, 1963- (Anderson, Taylor, 1963- Artillerymen series, 2023)
"After being stranded on a very different and more perilous Earth, Colonel Lewis Cayce led his small army of displaced Americans, natives of the Yucatán, and Jaguar Warriors to defeat the biggest host the Dominion general Agon could assemble. Most unexpectedly, General Agon came to recognize the inherent evil of the Dominion and its depraved Blood Priests and turned on his former leaders. Awkwardly at first, Lewis Cayce and Agon join forces to press their common enemy back toward the dark heart of the Dominion in the Great Valley of Mexico. But more Dominion troops have been drawn from the west to stop the Allied march on the Holy City, and a grueling race has begun. Worse, the Gran Cruzada-a vast Dom army that was marching on the far Californias to eject yet another heretic foe-might've already been recalled to face Cayce's soldiers. Time has become more precious than ever, and before Lewis Cayce can even try to implement his plan for total victory, he and his force must brave their greatest challenge yet-a brutal fight against a larger, better-trained army whose commander has a gift for strategy to rival Cayce's own. The struggle to keep all his soldiers alive, new friends and old comrades alike, will test Cayce like never before, and, win or lose, nothing will be the same"--